Cynical hostility increases whereas sense of coherence decreases the odds for current suicidal thoughts: A cross‐sectional study of the general adult population sample - Raimo Palmu; Timo Partonen (Health Science Reports, 2023)
Abstract Background and Aims Earlier, somatic diseases and mental disorders have been associated with cynical hostility as well as sense of coherence, but there is a gap of knowledge, whether they contribute to suicidality at population level. Methods A random sample of adults, representative of the general population living in Finland, participated in a nationwide health examination study. For 4387 participants aged 18–97 years, we analyzed, after controlling for confounding factors, whether cynical hostility, as assessed with the 8‐item Cook‐Medley Hostility Scale, or sense of coherence, as assessed with the 13‐item Sense of Coherence Scale, contributed to current suicidal thoughts during the past 7 days as scored on the 25‐item Hopkins Symptom Checklist. Results Suicidal thoughts (current thoughts of ending one's life) were associated significantly with cynical hostility (p < 0.001) as well as with sense of coherence (p < 0.001). Of the specific items of cynical hostility, the item “I am sure that most people do not have problems with lying for their own good” was associated most strongly with current suicidal thoughts (p < 0.001). Conclusion Cynical hostility predicted current suicidal thoughts in a population‐based sample of adults aged 18–97 years. Sense of coherence protected from current suicidal thoughts.